Waterproof bioelectrodes for electrophysiological interfacing applications - Ng, You Shan (2018)
The inadequate adhesion of underwater wearable devices on the skin is a major drawback for biomedical and healthcare industries. As a result, development of styrene-ethylene-butylene-styrene/polydopamine (SEBS/PDA) coated silk protein hydrogel film was initiated to synthesize waterproof and adhesive patchable devices for long term biomedical usage. In this study, the synthesis of SEBS/PDA coated silk protein hydrogel film had been achieved. Silk fibroin was first extracted by washing silk strands, followed by gelation of silk fibroin solution to obtain a silk protein hydrogel film. Subsequently, pH 8.5 dopamine solution was poured onto the silk protein hydrogel film and allowed to undergo oxidative polymerization to form a PDA coated silk protein hydrogel film (PDA/silk film). Thereafter, SEBS film was synthesized through an evaporation process and gold nanoparticles (AuNPs) were deposited onto the SEBS film by thermal evaporation, to form a SEBS/Au film. Lastly, the SEBS/Au film was adhered onto the PDA/silk film to form a SEBS/PDA coated silk protein hydrogel composite material. The effectiveness of the adhesive strength of the composite material in wet conditions was assessed based on whether the composite material can remain adhered onto the skin in water. With reference to the experimental results, SEBS/PDA coated silk protein hydrogel film was observed to have remained adhered onto the skin when fully submerged in water. Furthermore, the film was observed to be flexible as vigorous movements of the arm did not result in the film peeling off from the skin or surface cracks in the film. It also remained tightly adhered to the skin even when the arm was taken out of the water, this showed that the adhesive property was retained despite being exposed to a wet environment. This result demonstrated that the incorporation of silk fibres, bioinspired dopamine-based wet adhesives, AuNPs and SEBS to form a composite material, has a huge potential for the fabrication of waterproof and highly adhesive patches for electrophysiological applications. However, the results did not consider the effectiveness of the adhesion strength of the film to remain adhered onto the skin in various pH environments. Thus, future researches can aid to enhance the use of SEBS/PDA coated silk protein hydrogel film in varying pH environments, allowing the material to retain its adhesive properties in different pH environments and ensuring accurate and reliable medical diagnoses for long term usage.